Drop-out in fitness-sport. Comparing the general relevance of reasons for quitting - Zarotis, Georgios; Athanailidis, Ioannis; Tosunidis, A.; Mastrogiannopoulos, N. (Akademia Wychowania Fizycznego w Poznaniu)
Aim of Study. The central question of the present study is how strong are the various reasons for abandoning activities in a fitness studio. And to what extent these reasons differ from one another in terms of importance for the drop-out decision. We also examine whether there are typical priorities in the dropout justification and which reasons are used, in a statistically significant way, more or less or not at all. Material and Methods. A total of 225 people, who had terminated their contract with a fitness studio, were questioned. The survey was conducted as a telephone inquiry about their actual decision. The study was conducted in a health-oriented fitness centre in East Cologne. The fitness facility was opened in 1994 and has a size of 1,100 square metres. Results. At the time of the study, the gym had up to 1.151 memberships. Among them, 59% of the members were women and 41% were men. The average age of the respondents was 43.5 years. The average duration of membership added up to 4.4 years. Overall, it is found that only a few of the reasons offered in the survey are also indicated in significant frequency as important for the quitting decision. Conclusion. With the exception of membership costs, these reasons have nothing to do with studio conditions, but rather, apart from the mentioned health problems, mainly address issues of time scheduling and prioritizing the training in relation to other areas of life. The data show that the various quitting reasons were clearly evaluated differently by the respondents, and that there was apparently little generalized information on the motives of the quitting decision.
Keywords: drop out; members; fitness-sport